Genome-wide association study identifies novel susceptible loci and highlights Wnt/beta-catenin pathway in the development of adolescent idiopathic scoliosis - Zhu, Zezhang; Xu, Leilei; Leung-Sang Tang, Nelson; Qin, Xiaodong; Feng, Zhenhua; Sun, Weixiang; Zhu, Weiguo; Shi, Benlong; Liu, Peng; Mao, Saihu; Qiao, Jun; Liu, Zhen; et al. (Human molecular genetics, 2017)
The genetic architecture of adolescent idiopathic scoliosis (AIS) remains poorly understood. Here we present the result of a 4-stage genome-wide association study composed of 5,953 AIS patients and 8,137 controls. Overall, we identified three novel susceptible loci including rs7593846 at 2p14 near MEIS1 (Pcombined = 1.19 × 10-13, OR = 1.21, 95% CI = 1.10-1.32), rs7633294 at 3p14.1 near MAGI1 (Pcombined = 1.85 × 10-12, OR = 1.20, 95% CI = 1.09-1.32), and rs9810566 at 3q26.2 near TNIK (Pcombined = 1.14 × 10-11, OR = 1.19, 95% CI = 1.08-1.32). We also confirmed a recently reported region associated with AIS at 20p11.22 (Pcombined = 1.61 × 10-15, OR = 1.22, 95% CI = 1.12-1.34). Furthermore, we observed significantly asymmetric expression of Wnt/beta-catenin pathway in the bilateral paraspinal muscle of AIS patients, including beta-catenin, TNIK, and LBX1. This is the first study that unveils the potential role of Wnt/beta-catenin pathway in the development of AIS, and our findings may shed new light on the etiopathogenesis of AIS.